If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(7 + -12x) = 2 (7 * glo + -12x * glo) = 2 (7glo + -12glox) = 2 Solving 7glo + -12glox = 2 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -2 + 7glo + -12glox = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + 7glo + -12glox = 0 The solution to this equation could not be determined.
| 1+3y-y=y-4+2y | | 5y+3y-4=30 | | 6.2x+7.1x-y= | | Y=40x+-16x^2 | | .4y+7.96=2.24 | | (x+4y^2)dy+(y+x^2)dx=0 | | 28x^2-9x-1=0 | | 3x+13=-3x+73 | | (2v+14)(v^2-8v+12)=0 | | 14t+15=10t+31 | | 8x-1=642x | | 2t-7=t+2 | | z^2+(4+i)*z-6+6i=0 | | 6h+20=720 | | 2b-50+b+2b-2+30+b-25+44+b-22=360 | | 2n-15=45 | | -3(4+2)=4-22 | | 4n+12=7n+9 | | 3w-23+3w-33+4w+4w-46+49+3w-39+61=360 | | 2x*2x-9x+2=0 | | 2x+2(3x+1)+3x-1=7x+1 | | 6x+6=6x-5 | | 2x+45=x-32 | | 60.5+90+x=180 | | 3w-23+3w-33+4w-46+3w-39+49+61=360 | | 6(x+1)-(p+1)=6x+3 | | 7k^3+2x=0 | | 12s=16+6s+19 | | 7y-9=-2 | | x*x-4.5x+0.5=0 | | x(5x-6)=0 | | x^2-2=7-y^2 |